Toxicological effects of carbosulfan in rats: Antioxidant, enzymological, biochemical, and hematological responses. (July 2016) - Nwani, Christopher Didigwu; Agrawal, Narottam Das; Raghuvanshi, Suchita; Jaswal, Amita; Shrivastava, Sadhana; Sinha, Neelu; Onyishi, Grace; Shukla, Sangeeta
Carbosulfan is often used in agriculture for pest control on crops and for treatment against pyrethroid-resistant mosquitoes. This study investigated the impact of carbosulfan on oxidative stress markers, antioxidant defense, hematological, biochemical, and enzymological parameters in Sprague Dawley rats. Rats were orally administered carbosulfan doses of 1.02 to 10.20 mg/kg body weight daily; after 96 h, blood samples were taken, and the liver, kidney, and brain were dissected out for study. Results indicate that carbosulfan significantly increased the levels of lipid peroxidation and suppressed the activity of reduced glutathione, glutathione reductase, catalase, glucose-6-phosphate dehydrogenase, and adenosine triphosphatase. A mixed trend was observed in the activity of superoxide dismutase, while an increase was observed in the levels of serum uric acid, urea, aspartate aminotransferase, and alanine aminotransferase. Hemoglobin and albumin levels decreased but no significant differences were observed in creatinine and bilirubin levels. Future studies should include a more detailed analysis of the effects of chronic carbosulfan exposure on these biomarkers to further assess the impact of the pesticide on mammalian models.